Slope Stability Analysis Throughout Road Around Bukit Barisan Selatan National Park (BBSNP) using Fellenius Method - Radityo, Daniel; Bilal Al Farishi; Rezky Naufan Hendrawan; Alviyanda; Imam Ahmad Sadisun (UIR PRESS, 2024)
Bukit Barisan Selatan National Park (BBSNP) is a nature conservation area in Indonesia. The slope stability of the interprovincial roads in BBSNP needs to be assessed for slope stability. This study assesses slope stability using the Fellenius method for the factor of safety calculation. The data utilized consists of geological and structure regional conditions, soil descriptions, soil physical and mechanical properties, water content, liquid limit, plastic limit, plasticity index, specific gravity, soil strength, slope dimensions, and slope weight. The sampling process is conducted un-disturb, followed by laboratory testing. The laboratory tests conducted include soil elasticity and plasticity, soil cohesion, and internal friction angle. The critical slopes at LT-L01 and LT-L23 are compromised due to the low cohesion values, making both slopes susceptible to landslides. The stable slope at LT-R04, LT-L15, LT-L19, and LT-R30 exhibit variability properties across the slopes. The lithology for slope LT-R04 consists of inorganic clay with high plasticity, slopes LT-L15 and LT-R30 have same lithology of silty clay with medium plasticity, while slope LT-L19 has lithology of silty clay with low plasticity. The safety factor values indicate stability due to moderate - high cohesion, contributing to slope stability. Material compaction is required to enhance cohesion values on the slopes. Additionally, need to mitigate water saturation conditions in the slope materials.